Urinary Eicosanoid Metabolites in HIV-Infected Women with Central Obesity Switching to Raltegravir: An Analysis from the Women, Integrase, and Fat Accumulation Trial - Todd Hulgan; M. Sean Boger; Diana H. Liao; Grace A. McComsey; Christine A. Wanke; Alexandra Mangili; Sharon L. Walmsley; Heather McCreath; Ginger L. Milne; Stephanie C. Sanchez; Judith S. Currier; Jordan E. Lake (Hindawi Limited, 2014)
Chronic inflammation is a hallmark of HIV infection. Eicosanoids reflect inflammation, oxidant stress, and vascular health and vary by sex and metabolic parameters. Raltegravir (RAL) is an HIV-1 integrase inhibitor that may have limited metabolic effects. We assessed urinary F2-isoprostanes (F2-IsoPs), prostaglandin E2 (PGE-M), prostacyclin (PGI-M), and thromboxane B2 (TxB2) in HIV-infected women switching to RAL-containing antiretroviral therapy (ART). Thirty-seven women (RAL = 17; PI/NNRTI = 20) with a median age of 43 years and BMI 32 kg/m2 completed week 24. TxB2 increased in the RAL versus PI/NNRTI arm (+0.09 versus −0.02; P=0.06). Baseline PGI-M was lower in the RAL arm (P=0.005); no other between-arm cross-sectional differences were observed. In the PI/NNRTI arm, 24-week visceral adipose tissue change correlated with PGI-M (rho=0.45; P=0.04) and TxB2 (rho=0.44; P=0.005) changes, with a trend seen for PGE-M (rho=0.41; P=0.07). In an adjusted model, age ≥ 50 years (N=8) was associated with increased PGE-M (P=0.04). In this randomized trial, a switch to RAL did not significantly affect urinary eicosanoids over 24 weeks. In women continuing PI/NNRTI, increased visceral adipose tissue correlated with increased PGI-M and PGE-M. Older age (≥50) was associated with increased PGE-M. Relationships between aging, adiposity, ART, and eicosanoids during HIV-infection require further study.